Identifying roadblocks and improving strategies to foster new media technology adoption in extension - Tully, Kelsey Mae (Kansas State University, 2019)
Extension agents have been educating and serving their clientele for over 100 years. As the years have come and gone, advancements in agriculture and technology have grown immensely. With these developments, education and communication have come to the forefront of extension. New media technology, a result of technology advancements, has the potential to positively influence the way extension agents communicate and educate their targeted audience. However, new media technology adoption in extension has been a slow and tedious process. The purpose of this qualitative study was to examine Kansas extension agents’ use of new media technology and their decision process behind adopting or rejecting the use of new media technology, while also identifying potential roadblocks preventing adoption. This study was guided by three separate theories: diffusion of innovations, the theory-in-use model, and the model of strategic learning. The three theories were incorporated into a holistic model of technology adoption and used to guide the research. The initial participants for the study, Kansas agricultural extension agents, were recruited using a purposive sampling method through extension contacts. A quantitative survey was sent to all 98 Kansas agricultural extension agents and was used as a tool to identify agents to participate in semi-structured interviews. Based on participants’ survey responses, individuals were sorted into four groups of new media technology users (non, low, medium and high). Nine individuals were selected to participate in the qualitative semi-structured interviews. Participants were randomly selected for the low and medium user groups (the non-users and high user groups did not have enough participants for random selection). Interviews were transcribed by the researcher using the direct content analysis approach. The major themes that were discovered when it came to facilitation of new media technology in this study included: The relationship between relative advantage, compatibility, focusing and aligning; The relationship between complexity, trialability, observability and learning; The relationship between executing and Argyris and Schon’s model. While all Kansas agricultural extension agents agreed that the use of new media technologies was imperative to stay relevant, they were not equally eager to adopt the technologies. Identified roadblocks to the adoption of new media technology included: time, personal attitude, efficiency of communication, inconsistencies in new media technologies, and ethics. This study offers possible solutions for overcoming the identified barriers to implementing new media technology and also proposes a new holistic approach to technology adoption.
Keywords: Kansas agriculture extension; New media technology; Technology adoption; Technology adoption barriers; Diffusion of innovations; Communication